2013
DOI: 10.5539/ijc.v5n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Electrolyte Containing AlBr3 and KBr for Rechargeable Aluminum Batteries

Abstract: The reversible redox reaction of Al 3+ /Al or Al deposition/dissolution was investigated in ethylbenzene containing AlBr 3 and KBr as an electrolytic solution for rechargeable aluminum batteries. KBr as a supporting electrolyte was also necessary for the reversible Al deposition/dissolution. This reversible redox reaction was observed on both glassy carbon (GC) and Pt electrodes. However, the charge/discharge tests showed that the GC and Pt electrodes had different ratios of discharge capacity to charge capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A rechargeable aluminium‐ion battery (AIB) is one of the new prototypes of secondary batteries because of its unique advantages, such as low cost, well‐defined change/discharge plateaus, and high specific energy and power density . As the anode of AIBs, metal aluminium is the most abundant metal element in the earth crust and possesses approximately four‐fold volumetric capacity (8040 mA h cm −3 ) in comparison with metal lithium (2062 mA h cm −3 ) . In the early efforts, a variety of cathode materials, including V 2 O 5 , VO 2 , anatase TiO 2 , fluorinated natural graphite, polymers, and copper hexacyanoferrate, have been widely explored, while they were found to be substantially restricted from practical applications due to low capacity, low voltage plateau, and limited cycle life.…”
Section: Introductionmentioning
confidence: 99%
“…A rechargeable aluminium‐ion battery (AIB) is one of the new prototypes of secondary batteries because of its unique advantages, such as low cost, well‐defined change/discharge plateaus, and high specific energy and power density . As the anode of AIBs, metal aluminium is the most abundant metal element in the earth crust and possesses approximately four‐fold volumetric capacity (8040 mA h cm −3 ) in comparison with metal lithium (2062 mA h cm −3 ) . In the early efforts, a variety of cathode materials, including V 2 O 5 , VO 2 , anatase TiO 2 , fluorinated natural graphite, polymers, and copper hexacyanoferrate, have been widely explored, while they were found to be substantially restricted from practical applications due to low capacity, low voltage plateau, and limited cycle life.…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of medium-low temperature bath for Al and Al-alloy electroplating have been reported [2]: they include organic solvents (e.g. ethers [3,4], aromatic hydrocarbons [5][6][7][8][9], sulfones [10][11][12][13][14][15][16][17][18] and others [19,20]), and ionic liquids [21][22][23][24][25][26][27][28][29], to name only a few. Some of them are applied to improve the corrosion resistance of magnesium alloys and steel [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…6,7,22 A previous spectroscopic study on 1.7 mol dm ¹3 diglyme solution of AlCl 3 (cf. 1.4 mol dm ¹3 in this study) showed that the system consists of molecular species (AlCl 3 ·diglyme) and ionic ones of four-Cl-coordinated AlCl 4 ¹ and six-O/Cl-coordinated [AlCl 2 (diglyme) 2 ] + .…”
Section: ¹2mentioning
confidence: 99%
“…Besides, the media range from high temperature molten salts, 3 organic solvents e.g. ethers, 4,5 aromatic hydrocarbons, [6][7][8][9] and dimethylsulfone (DMSO 2 ), [10][11][12][13][14][15] and ionic liquids (ILs). [16][17][18][19][20][21] Although the high temperature baths have mainly been used for industrial Al electrorefining, medium-low and/or room temperature (RT) baths are anticipated as promising Al electroplating and/or Al battery electrolytes.…”
Section: Introductionmentioning
confidence: 99%